2012
DOI: 10.1155/2012/398720
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxidative Stress and Physiological Damage in Daphnia magna by Copper in the Presence of Nano‐TiO2

Abstract: This study examines the potential hazard of an individual nanomaterial on the Cu biotoxicity to aquatic organisms.Daphnia magnain the absence or presence of nano-TiO2was exposed to Cu. Maintaining nano-TiO2at a safe concentration cannot eliminate its potential hazard. The biomarkers superoxide dismutase, catalase, and Na+/K+-ATPase inD. magnawere measured. Cu in the presence of nano-TiO2induced higher levels of oxidative stress and physiological damage because of the sorption of Cu. Nano-TiO2also caused Na+/K+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…There are a number of studies indicating alteration of catalase activity induced by different chemicals in aquatic animal species including D. magna (Ahmad et al, 2005;Kim et al, 2010b;Fan et al, 2012;Sarkar et al, 2014). The present study showed that daphnids exposed to H 2 O 2 alone showed increased CAT production which was more pronounced at the higher concentration of the oxidant after 6 h of exposure.…”
Section: Catalase Activitysupporting
confidence: 49%
See 1 more Smart Citation
“…There are a number of studies indicating alteration of catalase activity induced by different chemicals in aquatic animal species including D. magna (Ahmad et al, 2005;Kim et al, 2010b;Fan et al, 2012;Sarkar et al, 2014). The present study showed that daphnids exposed to H 2 O 2 alone showed increased CAT production which was more pronounced at the higher concentration of the oxidant after 6 h of exposure.…”
Section: Catalase Activitysupporting
confidence: 49%
“…Our present study revealed that daphnids subjected to H 2 O 2 alone showed the decreased heart rate with increasing time of exposure. On the basis of the results obtained in mammals it may be hypothesized that the inhibited heart rate is a result of oxidative stress-induced dysfunction of vital enzymes for heart contraction, such as Na + /K + -ATPase (Ostadal et al, 2004;Fan et al, 2012). On the other hand, the animals treated with the combinations of H 2 O 2 + ECT showed less depressed heart rate indicating protective activity of the amino acid against H 2 O 2 which may result from ECTinduced stabilization of Na + /K + -ATPase or other cardiac proteins.…”
Section: Heart Rate and Thoracic Limb Movementmentioning
confidence: 99%
“…This effect may result from the oxidative modification of contractile enzymes in the heart muscle. This hypothesis is supported by the data obtained from studies performed on mammals suggesting that the depression of Na + /K + -ATPase may be a result of oxidative stress (Ostadal et al 2004;Fan et al 2012). We also found that the animals exposed to the combinations of FA+ECT showed less depressed heart rates suggesting that the amino acid may protect cardiac proteins from FA-induced oxidation.…”
Section: Heart Rate and Thoracic Limb Movementsupporting
confidence: 85%
“…There are a number of studies showing changes of catalase activity induced by different chemicals in Daphnia magna (Ahmad et al 2005;Kim et al 2010b;Fan et al 2012;Sarkar et al 2014). FA is oxidised by catalase with the use of hydrogen peroxide (van Dijken et al 1975).…”
Section: Catalase Activitymentioning
confidence: 99%
“…Some reports have studied the possible combined effects from the interaction of nano-TiO 2 with other pollutants (Sun et al, 2009;Hu et al, 2011;Fan et al, 2012). For instance, a previous study focused on the bioconcentration of the e-waste (BDE-209) that can be absorbed by nano-TiO 2 .…”
Section: Introductionmentioning
confidence: 99%